2010
DOI: 10.1080/14786410802270779
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HSV activity of camptothecin analogues

Abstract: In order to explore the range of biological activities of the camptothecin compound class, the in vitro antiviral efficacies of series I-IV of representative members from camptothecin analogues on herpes simplex virus type 2 (HSV-2) were evaluated on vero cells. Several compounds exhibited similar or better antiviral activity against HSV-2 in vitro than acyclovir. Among them, compound 6 showed the highest anti-HSV-2 activity, with IC(50) values of 1.3 microg mL(-1) and SI values of 27.04, respectively. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In ancient China, the crude extract of Camptotheca acuminate containing CPT has been used traditionally to control insect pests for centuries, and it was reported to be a potent chemosterilant against the housefly and cabbage caterpillar. 103,104 It also exhibited significant inhibitory activities against several agricultural pests such as Empoasca vitis, Mythimna separate Walker, Brevicoryne brassicae, Nilaparvata lugens, and Chilo suppressalis, supporting its potential use as a field pesticide. [105][106][107][108] Additionally, a recent study showed that CPT could cause visible changes in the midguts from the lepidopteran pests Trichoplusia ni and Spodoptera exigua, such as losing the single layer of epithelial cells and disrupting the peritrophicmembrane.…”
Section: Pesticidal Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…In ancient China, the crude extract of Camptotheca acuminate containing CPT has been used traditionally to control insect pests for centuries, and it was reported to be a potent chemosterilant against the housefly and cabbage caterpillar. 103,104 It also exhibited significant inhibitory activities against several agricultural pests such as Empoasca vitis, Mythimna separate Walker, Brevicoryne brassicae, Nilaparvata lugens, and Chilo suppressalis, supporting its potential use as a field pesticide. [105][106][107][108] Additionally, a recent study showed that CPT could cause visible changes in the midguts from the lepidopteran pests Trichoplusia ni and Spodoptera exigua, such as losing the single layer of epithelial cells and disrupting the peritrophicmembrane.…”
Section: Pesticidal Activitymentioning
confidence: 96%
“…In ancient China, the crude extract of Camptotheca acuminate containing CPT has been used traditionally to control insect pests for centuries, and it was reported to be a potent chemosterilant against the housefly and cabbage caterpillar . It also exhibited significant inhibitory activities against several agricultural pests such as Empoasca vitis, Mythimna separate Walker, Brevicoryne brassicae , Nilaparvata lugens , and Chilo suppressalis , supporting its potential use as a field pesticide .…”
Section: Biological Activity Of Cpt and Related Derivativesmentioning
confidence: 99%
“…Although these agents have proven to be efficacious in the treatment of HSV infections, the risk of adverse effects and the frequent development of drug‐resistant strains of HSV make it imperative to discover new antiviral agents with lower toxicity, more convenient regimens, and less susceptible to resistance emergence. Several viral and cellular products have been investigated in recent years to find different targets with different mechanisms of action, and literature has been filled by scientific reports of the in vitro anti‐herpetic activity of a wide variety of natural products and synthetic compounds .…”
Section: Anti‐herpetic Drugs: Identification and Development Of Peptimentioning
confidence: 99%
“…Herpes simplex viruses (HSV-1) infection may result several diseases such as genital herpes, labial herpes and chronic mucocutaneous ulceration [12,13]. HSV infections are usually treated with nucleoside analogues such as acyclovir [14]. However, the efficacy of these drugs is limited by the recent increase in the resistance of virus and recurrence of latent virus [15].…”
Section: A N U S C R I P Tmentioning
confidence: 99%